Penerapan Bimbingan Konseling Untuk Meningkatkan Potensi Minat dan Moral Peserta Didik di SMP Clarissa Batam - Ardianto lahagu; Bestiniat Harefa; Amanda Simanjuntak; Fauzi Hutagalung; Donni Fernando Sihite; Elfrida Elena Br Silaban; Rondal Sianipar; Titin Aritonang; Nora Rury Febrina Manalu; Melisa Meli; Juniarta Siburian; Nelva Sitorus (Universitas 17 Agustus 1945 Semarang, 2023)
Judging based on the results of observations made by the PKM team at Clarissa Batu Aji Middle School, the team found the problem that some students still did not understand the importance of counseling guidance in schools, which was caused by the thinking factors of participants who considered counseling to be scary and unimportant. The purpose of implementing this PKM is to provide students with an understanding of the importance of counseling guidance. The application of counseling guidance has benefits that include several things, namely: achieving positive mental health, individual effectiveness, ability to make decisions, and changes in behavior. In this case, it will help students to explore and increase their potential. The implementation of this PKM uses the method of observation, implementation of activities, and evaluation. The results obtained are students are able to better understand the importance of counseling guidance to increase the potential of interest and morale